Semantic Annotation of Image Resources in Digital Humanities - CHEN Tao, SHAN Rongrong, LI Hui (Nongye tushu qingbao xuebao, 2020)
[Purpose/Significance] A large number of image resources in digital humanities have not been in effective use for a long time, and the phenomenon of "isolated image islands" is intensifying. The International Image Interoperability Framework (IIIF) opens a new window for more in-depth interactions with image applications. Image annotation is the key to breaking image islands and enhancing image recognition. [Method/Process] Based on IIIF framework, this paper proposes three dimensions of image annotation: image-level metadata injection, object-level content transcription, and semantic-level deep annotation connection. At the same time, the ontology management platform built in the paper provides ontology support for semantic annotation of image resources. [Results/Conclusions] This paper takes Night-Shining White, a monochrome ink-on-paper painting by Han Gan, as an example. In this case, the paper discusses the new interactive experience and research mode brought by the use of image annotation and IIIF technology in semantic enhancement of images, object tag clustering and precise associations of resources. It indicates that the combination of IIIF, linked data and artificial intelligence (AI) is bound to open a new era of digital humanities research.